LHFPL5 is required for maximal activation of the mechanotransduction channel in cochlear hair cells - Xufeng Qiu; Jose P. Llongueras; Lili Yin; Christopher Cunningham; Ulrich Müller (Proceedings of the National Academy of Sciences, 2025)
Mechanoelectrical transduction (MET) channels in cochlear hair cells are gated by tip links through a mechanism that is poorly defined. LHFPL5 interacts with the tip-link component PCDH15 and the MET-channel component TMC1, suggesting that LHFPL5 regulates channel activation by mechanical force. To test this hypothesis, we analyzed MET in hair cells from mice expressing an LHFPL5 mutant protein lacking three N-terminal amino acids. These mutant mice suffer from recessive deafness, and MET is drastically impaired in cochlear hair cells. The resting open probability of the MET channels is increased in the mutants, while unitary channel conductance, adaptation, and tonotopic channel properties remain unaltered. Unlike in other LHFPL5 mutants, MET channel proteins are still present at normal levels in stereocilia of mutant mice. We conclude that LHFPL5 is required for maximal mechanical activation of MET channels in cochlear hair cells thereby affecting the hair bundle sensitivity to mechanical stimulation and thus the sound sensitivity of the auditory sense organ.